The Optimization of Capacity Boiler Efficiency 26 Tons/Hours With Fuel Alumination and Statistical Product and Service Solutions (SPSS) Analysis - Istianto Budhi Rahardja; Masnia Masnia (ADI Publisher, 2021)
The boiler is a steam-producing installation that is used to drive steam turbines as power plants in palm oil mills. It is working to remove the heat generated by fuel into the form of steam containing enthalpy, which is used to drive a steam turbine.This study was conducted for 15 days started from May 27, 2017, until June 15, 2017. The location of the study was conducted at PMKS South Sumatra Province. The average boiler efficiency is 81% with a heating value of 2117.6717 kcal/kg compared to other dates that have a higher heating value but efficiency is below 80%. This shows the success of the boiler's performance is not only determined by the heating value contained in the fuel but also determined by the temperature of the feedwater entering the boiler, the amount of fuel in the boiler and the condition of the fuel in the boiler combustion chamber.